INDUCTION EFFECT OF MICROALGAE SCENEDESMUS DIMORPHUS AGAINST HEMATOLOGY ON MICE (MUS MUSCULUS) SUFFERING ANEMIA DISEASES - Armaini, Armaini; Salim, Marniati; Pribadi, Panji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aims to investigate the potential of Scenedesmus dimorphus as a cure for aplastic anemia in mice (Mus musculus). Methods: Fifty male mice divided into five groups, mice suffering anemia due to induction of chloramphenicol. Oral administrated of S. dimorphus for 28 days with a dose of 2.5 g/50 ml, 5.0 g/50 ml, and 7.5 g/50 ml, respectively, to cure aplastic anemia in mice and samcobion as standard drug. Results: Induction of chloramphenicol caused the mice to suffering aplastic anemia and weight loss in mice. Biomass of S. dimorphus has an effect of against hematological parameters and total blood count estimation. The result shows significant (p<0.05 ANOVA) on weight gain, an increase of erythrocyte counts, and hemoglobin level, whereas an increase of hematocrit and reticulocyte values have non-significant, and a dose of S. dimorphus 5.0 g/50 ml were the treatment most effective for anemia in mice. Conclusion: Based on the results of this study, S. dimorphus biomass has the healing benefit of aplastic anemia due to the administration of chloramphenicol.